Pengaruh Influencer Marketing dan Kualitas Produk terhadap Minat Beli Konsumen Produk Skintific pada Pengguna E-Commerce di Jakarta Pusat - Adi Rahmawan; Purwatiningsih Purwatiningsih; Ratih Setyo Rini (Manajemen Kreatif Jurnal, 2025)
This study aims to determine the effect of Influencer Marketing and product quality on buying interest in e-commerce users in Central Jakarta. This research uses descriptive research with a quantitative approach, namely the author describes the phenomena that exist in the formulation of problems that have been determined based on data that has been collected from primary sources. Data collection was obtained through distributing questionnaires online to e-commerce users in Central Jakarta. The sample used in this study amounted to 100 respondents. The sampling technique used was purposive sampling, then processed using SPSS 25 with multiple linear data analysis techniques. The results showed that Influencer Marketing and product quality partially had a positive and significant effect on buying interest. Furthermore, Influencer Marketing and product quality simultaneously have a positive and significant effect on buying interest in e-commerce users in Central Jakarta. This proves that Influencer Marketing and product quality are effective strategies in influencing consumer buying interest in products or services.